Flipped Classroom Limited Face-to-Face Learning: A Bibliometric Study - Joko Soebagyo; Saamah Saamah (STAI Hubbulwathan Duri, 2023)
The writing of this article is motivated by the government's policy of limiting learning activities in schools due to the covid-19 pandemic that has not ended. This research first revealed articles related to flipped classroom on mathematics learning to explore themes and opportunities for future research. The research method uses bibliometric analysis assisted by Publish or Perish (PoP) and VOSviewer. With the google scholar database study, there are research articles about flipped classrooms published in scientific journals in the last ten years starting from 2011 to 2021. The keywords used are related to the application of flipped classroom to mathematics learning during the Limited Face-to-Face Learning (PTMT) period. Search results obtained 500 articles, and after selection, 428 articles were obtained that qualified as samples. The selection results on PoP are stored in RIS form and analyzed using VOSviewer with the full counting method so that 2870 terms are obtained. Verification is carried out by selecting terms that are relevant and intersect with the theme and eliminate those that do not match. The results of bibliometric analysis related to flipped classroom in mathematics learning show that variables with research potential in the future are flipped classroom approach, flipped classroom methods, mathematical concept, combination, impact, evectiveness and learning process.